PARALYMPIC GAMES: HISTORY AND SYMBOLS OF DEVELOPMENT (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article analyzes the history of the origin of the Paralympic Games with their symbols and the order in which they were held.